2022
DOI: 10.1002/hsr2.754
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associations of depression, anxiety, and stress among people living with HIV: A hospital‐based analytical cross‐sectional study

Abstract: Background and Aims An important but much less researched burden of human immunodeficiency virus (HIV) in Sub‐Saharan Africa includes the associated mental health outcomes of living with the virus. This study aimed to estimate the prevalence of depression, anxiety, and stress, and describe some of the socio‐demographic associations among people living with HIV (PLHIV) in Ghana. Methods A cross‐sectional study was conducted at the Cape Coast Teaching Hospital, Ghana. Sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 30 publications
0
4
0
1
Order By: Relevance
“…Otro hallazgo de este estudio fue que las personas que profesan la religión evangélica y los agnósticos (quienes no profesan ninguna religión) presentan mayor puntaje de estrés, ansiedad y depresión en comparación con quienes se consideran católicos. Este hallazgo discrepa con un estudio realizado en Ghana durante la pandemia por covid-19, en el cual reportan que no existe diferencias entre el porcentaje de pobladores que presentan estrés, ansiedad y depresión según el tipo de religión que profesan (cristianos, islámicos y agnósticos) (31) . Es probable que esta diferencia sea debido a las diferencias culturales entre países latinoamericanos y africanos.…”
Section: Discussionunclassified
“…Otro hallazgo de este estudio fue que las personas que profesan la religión evangélica y los agnósticos (quienes no profesan ninguna religión) presentan mayor puntaje de estrés, ansiedad y depresión en comparación con quienes se consideran católicos. Este hallazgo discrepa con un estudio realizado en Ghana durante la pandemia por covid-19, en el cual reportan que no existe diferencias entre el porcentaje de pobladores que presentan estrés, ansiedad y depresión según el tipo de religión que profesan (cristianos, islámicos y agnósticos) (31) . Es probable que esta diferencia sea debido a las diferencias culturales entre países latinoamericanos y africanos.…”
Section: Discussionunclassified
“…Inequities related to race, socioeconomic status, sex identity, and sexual orientation are risk factors associated with accelerated aging, which may be further exacerbated in PLWH [26,27]. Cultural and epidemiological stigmatism related to both age and HIV status can contribute to disproportionate access to healthcare, impede optimal time to diagnosis, and lead to increased rates of anxiety, depression, and stress [28]. Culturally informed and comprehensive social services need to be an essential part in the continuum of care for older PLWH to mitigate health disparities that can contribute to variations in biological age progression.…”
Section: Factors Influencing Aging Trajectoriesmentioning
confidence: 99%
“…The population of people living with HIV is shifting towards an older demographic and consequentially are at heightened risks for comorbidities, multimorbidity, and geriatric syndrome. contribute to disproportionate access to healthcare, impede optimal time to diagnosis, and lead to increased rates of anxiety, depression, and stress [28]. Culturally informed and comprehensive social services need to be an essential part in the continuum of care for older PLWH to mitigate health disparities that can contribute to variations in biological age progression.…”
Section: Key Pointsmentioning
confidence: 99%
“…Higher rates of depressive and anxiety symptoms have been reported amongst FLWHA in several studies [ 3 7 ]. For instance, 82% of survey respondents in a study of 832 FLWHA from 94 countries reported having symptoms of depression, and participants indicated that their mental health concerns rose 3.5-fold after receiving an HIV diagnosis [ 14 ].…”
Section: Introductionmentioning
confidence: 96%
“…Mental health conditions affect females living with HIV and AIDS (FLWHA) at substantially higher rates compared with men living with HIV and AIDS (MLWHA) and HIV-negative women [3][4][5][6]. Thus, the established gender disparity in mental health disorders such as depression and anxiety is disproportionately increased in the context of HIV and AIDS [7].…”
Section: Introductionmentioning
confidence: 99%